A new animal model for delayed osseous union secondary to osteitis. Issue 1 (December 2015) - Helbig, Lars; Guehring, Thorsten; Rosenberger, Svenja; Ivanova, Adriana; Kaeppler, Kathrin; Fischer, Christian; Moghaddam, Arash; Schmidmaier, Gerhard
Abstract Background The treatment of infection-related delayed bone unions is still very challenging for the orthopedic surgeon. The prevalence of such infection-related types of osteitis is high in complex fractures, particularly in open fractures with extensive soft-tissue damage. The aim of this study was to develop a new animal model for delayed union due to osteitis. Methods After randomization to infected or non-infected groups 20 Sprague–Dawley rats underwent a transverse fracture of the midshaft tibia. After intramedullary inoculation with staphylococcus aureus (103 CFU) fracture stabilization was done by intramedullary titanium K-wires. After 5 weeks all rats were euthanized and underwent biomechanical testing to evaluate bone consolidation or delayed union, respectively. Micro-CT scans were additionally used to quantitatively evaluate the callus formation by the score of Lane and Sandhu. Blood samples were taken to analyze infectious disease markers (day 1, 14 and 35). Results Biomechanical testing showed a significant higher maximum torque in the non-infected group 5 weeks postoperatively compared with the infected group (p < 0.001). According to the Lane and Sandhu score a significantly higher callus formation was found in the non-infected group (p < 0.001). Similarly, the leucocyte count in the infected group was significantly higher than in the non-infected group (p < 0.05). Conclusions Here we have established a new animal model for delayed osseous union secondary to osteitis. The animal model appears to be appropriate for future experimental studies to test new therapeutic strategies in these difficult to treat bone healing complications.